Copyright Liability for Unauthorized Film Distribution via Illegal Streaming Websites: The Case of LK21 - Ayu Diah Nurrahma; Fairuz Nahdah; Sazkia Nurul 'Aini (LPPM Universitas Harapan Bangsa, 2026)
Film piracy through illegal streaming websites such as LK21 continues to erode industry revenue, weaken production incentives, and generate layered questions of liability. This article analyzes the construction of copyright liability for unauthorized film distribution via LK21 and formulates dispute-resolution and countermeasure directions that are relevant to copyright enforcement in Indonesia. This research adopts a normative legal method using statutory, conceptual, and case approaches. Primary legal materials include Law Number 28 of 2014 on Copyright, Law Number 33 of 2009 on Film, and regulations governing the handling of copyright infringement in electronic systems, while secondary legal materials are drawn from relevant scholarly literature and academic articles. The analysis is qualitative and employs grammatical, systematic, and teleological interpretation to examine the relationship between legal norms and the operational patterns of illegal streaming websites. The results indicate that providing access to films through LK21 correlates with infringements of economic rights, particularly reproduction and communication to the public, and may also affect moral rights when the integrity and attribution of works are disregarded. The discussion underscores the need for a liability mapping based on contribution-control parameters to assess the roles of uploaders, site operators, infrastructure providers, and advertising networks through their control over access and their receipt of economic benefits. The article recommends a synergistic combination of administrative, civil, and criminal enforcement complemented by strategies to disrupt monetization in order to curb the re-emergence of mirror domains and strengthen enforcement effectiveness.